Correlation between body mass index and blood pressure in urban school-going children of age 6–14 years - Mehta, Swati; Masand, Rupesh; Natani, Bhagwan Sahai; Verma, Chaman Ram; Singh, Sushmita (Indian Journal of Child Health, 2020)
Background: Obesity and hypertension (HT) have been on a rise in children. Both are associated with the increased cardiovascular disease risk and related morbidity and mortality in adulthood. Objectives: The objectives of the study were to determine the body mass index (BMI) and blood pressure (BP) of school-going urban children and to find out the correlation between BMI and BP. Materials and Methods: This study was performed on 1000 healthy school-going children (492 males and 508 females). BMI and BP were determined and recorded. Relevant statistical analysis was performed to divulge the relationship. Results: A significant (p